Analisa Kimia Bakpia Kering Substitusi Tepung Kulit Buah Naga - Amelia Nirmalawaty; Anak Agung Putu Sri Mahayani (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2020)
The potential of red dragon fruit peels both in terms of antioxidant activity and as sufficient food coloring promising. On the other hand antioxidants, one of which is vitamin C, is very susceptible to high heat. This study aims to determine the content of proximate, fiber and vitamin C from dry bakpia substitution of dragon fruit peels flour. A randomized block design with 4 replications was selected in this study, while the treatment consisted from 3 levels of dragon fruit peels flour substitution, namely 1%, 2%, 3% and control (0%). The results showed substitution of dragon fruit peels flour has no effect on water content, protein, fat, fiber and vitamin C dry bakpia. The 3% substitution of dragon fruit peels flour produces lower carbohydrate levels and significantly different with control, 1% and 2%. The ash content of 3% substitution of dragon fruit peels flour is higher and than significantly different with control and 1% but not significantly different with 2% . The conclusion was substitution of dragon fruit peels flour can be applied to 1- 2% of flour need to increase its nutritional value. Keywords: dragon fruit peels flour, dried bakpia, proximate, fiber, vitamin C